A Report on the Use of Public Funds to Develop and Support Community Organization Activities Among Seasonal and Migrant Farm Workers in California 1967 - American Friends Service Committee::::::; Mary Norment::::::; Nicholas Seidita::::::; Peter Lauwerys:::::: (1968)
An appendix containing reports outlining various studies conducted for the Farm Workers Opportunity Project. This includes a medical report, a special testing report, and demographic statistics.